Penyelesaian Permasalahan Non Linear dengan Pendekatan Linearisasi Dua Fase - Maharani Safitri; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2020)
Abstract—A nonlinear optimization problems with complicated nonlinear objective functions with nonlinear constraints is difficult to complete analytic but can be solved numerically. Research is conducted to seek solution of non-linear with constrained or not problems using a two-phase linearization approach. The result of this research is the solution of non-linear problems of minimum or maximum occupancy of the smallest residue.Keywords—Linear Programming Problems, Nonlinear Programming Problems, Linearization Approach, Taylor Series, Maclaurin series.